Colds, flu and coughing: a review of over-the-counter cold and flu medicines - J. Van Schoor (South African Family Practice)
The common cold is the most frequent human illness, and may be caused by several families of viruses, particularly the more than 100 serotypes of rhinoviruses. Inaccurate perceptions that antibiotics improve patient outcomes fuel the number of doctor visits and requests for antibiotics. The inappropriate use of antibiotics for minor, self-limiting, usually viral, upper-respiratory tract infections does not alter the course of the disease, and adds to the burden of antibiotic resistance. In addition, there is also no evidence to suggest that antibiotics prevent secondary bacterial complications following viral upper-respiratory tract infections. While most over-the-counter cold and flu remedies have no proven efficacy, they appear to attenuate the immune response to the infecting virus, and there is little doubt that appropriate symptomatic treatment can make the patient feel better. Therefore, symptomatic therapy remains the mainstay of common cold treatment. This article briefly reviews the components of cold and flu remedies, and provides a symptom-based assessment for the selection of appropriate over-the-counter medicine.